Yours cheerfully eaudiobook A novel. - Pearce, AJ (Emmy Lake Chronicles., 2021)
From the author of the "jaunty, heartbreaking winner" ( People ) and international bestseller Dear Mrs. Bird comes a charming and uplifting novel set in London during World War II about a plucky young journalist and her adventures as wartime advice columnist. London, November 1941. Following the departure of the formidable Henrietta Bird from Woman's Friend magazine, things are looking up for Emmeline Lake as she takes on the new challenges as a wartime advice columnist. Her relationship with boyfriend Charles is blossoming, while Emmy's best friend Bunty, still reeling from the very worst of the Blitz, is bravely looking to the future. Together, the friends are determined to Make a Go of It. When the Ministry of Information calls on Britain's women's magazines to help recruit female workers to the war effort, Emmy is thrilled to step up and help. But when she and Bunty meet a young mother who shows them the very real challenges that women war workers face, Emmy must confront a dilemma between doing her duty and standing by her friends. As funny, heartwarming, and touching as Dear Mrs. Bird , Yours Cheerfully is an endearing portrait of female friendship and "a fruitful exploration of the solidarity among women in times of grief, love, and hardship" ( Publishers Weekly ).